2010
DOI: 10.3846/bjrbe.2010.12
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Concrete Cracking Effect in Deck Slab of Continuous Bridges

Abstract: Analysis of the literature has shown that two main factors, which should be taking into consideration in designing of continuous bridges, are the influence of cracking on serviceability of the structures and inelastic behaviour of structural elements. Crack control is often the governing design criterion for the choice of the amount of longitudinal pre-stressing of reinforced concrete bridges as well as for the construction sequence of composite bridges. Present paper investigates cracking behaviour of reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…The latter represent the global response of structure with smeared out local effects such as the cracking, slippage and degradation of bond stresses. Numerous studies have shown that bond-stresses degrade with an increase in load (Torres et al 2004;Kaklauskas et al 2009Kaklauskas et al , 2011aWu, Gilbert 2009;Gribniak et al 2010;Kala et al 2010;Ng et al 2010;Zanuy 2010;Ho, Peng 2011). This also can be observed from the moment-curvature diagrams shown in Fig.…”
Section: Simplified Discrete Crack Modelsupporting
confidence: 59%
“…The latter represent the global response of structure with smeared out local effects such as the cracking, slippage and degradation of bond stresses. Numerous studies have shown that bond-stresses degrade with an increase in load (Torres et al 2004;Kaklauskas et al 2009Kaklauskas et al , 2011aWu, Gilbert 2009;Gribniak et al 2010;Kala et al 2010;Ng et al 2010;Zanuy 2010;Ho, Peng 2011). This also can be observed from the moment-curvature diagrams shown in Fig.…”
Section: Simplified Discrete Crack Modelsupporting
confidence: 59%
“…The application of the stochastic modeling procedure is shown, using the results of two RC ties tested by R. Kupliauskas and reported in Gribniak et al. (). The tests included shrinkage recordings.…”
Section: Modeling Examplementioning
confidence: 99%
“…Adequate account of the serviceability behavior and the parameters involved in the post-cracking behavior is of major importance for the design of RC structures (Bischoff 2007;Baena et al 2011;Gribniak et al 2010;Kaklauskas et al 2012). Due to the mechanical properties of FRP materials, the Serviceability Limit States (SLS) may govern the design of FRP RC elements (ISIS Canada 2001;Matthys, Taerwe 2000;Nanni 2003;Saikia et al 2007;Rafi, Nadjai 2009).…”
Section: Introductionmentioning
confidence: 99%